2015
DOI: 10.1016/j.envsoft.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multi-reservoir optimization modeling for real-world complexity with application to the Three Gorges system

Abstract: a b s t r a c tHigh dimensionality in real-world multi-reservoir systems greatly hinders the application and popularity of evolutionary algorithms, especially for systems with heterogeneous units. An efficient hierarchical optimization framework is presented for search space reduction, determining the best water distributions, not only between cascade reservoirs, but also among different types of hydropower units. The framework is applied to the Three Gorges Project (TGP) system and the results demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Therefore, it was concluded that SFLA outperforms the GA and PSO. Li et al (2014) applied seven heuristic algorithms to minimize the amount of water use and maximize the total power generation by the Three Gorges Reservoir, including the binary-coded GA, PSO, SA, dynamically dimensioned search (DDS), dynamic coordinate search using response surface models (DYCORS), and stochastic radial basis function method (SRBF). The latter authors concluded that PSO performed best in optimizing two objectives of the selected case study, which occurred due to increase in diversity of solutions and less dependent on the previous generation compared with other discussed approaches.…”
Section: The Binary-coded Gamentioning
confidence: 99%
“…Therefore, it was concluded that SFLA outperforms the GA and PSO. Li et al (2014) applied seven heuristic algorithms to minimize the amount of water use and maximize the total power generation by the Three Gorges Reservoir, including the binary-coded GA, PSO, SA, dynamically dimensioned search (DDS), dynamic coordinate search using response surface models (DYCORS), and stochastic radial basis function method (SRBF). The latter authors concluded that PSO performed best in optimizing two objectives of the selected case study, which occurred due to increase in diversity of solutions and less dependent on the previous generation compared with other discussed approaches.…”
Section: The Binary-coded Gamentioning
confidence: 99%
“…These decision variables are subjected to the following constraints: the radii of the Gaussian functions range from 0 to 1, the center coordinate of each function has the range 21 to 1, and the weighted combinations are non-negative and sum to 1 [Busoniu et al, 2011]. A genetic algorithm (GA) was linked with the system model in order to optimize system performance, as evolutionary algorithms have been shown to perform well for the optimization of reservoir operation [Giuliani et al, 2015;Li et al, 2015;Tsoukalas and Makropoulos, 2015;Yang et al, 2015].…”
Section: Assessing Optimized System Performancementioning
confidence: 99%
“…Meanwhile, when solving a MLGS problem, many complex constraints must be taken into account. These complex constraints and the conflicting objectives of annual hydropower generation and ecological flow demands make MLGS problems difficult to solve (Al-Aqeeli et al 2016;Feng et al 2018;Li et al 2015b). Therefore, this paper focuses on the MLGS problem of a CHS in which maximum annual hydropower generation and minimum annual ecological underflow and overflow water volume are considered simultaneously when satisfying a set of complex constraints.…”
Section: Introductionmentioning
confidence: 99%